Influence of mix design and tailoring on thermal performance of geopolymers - Lahoti, Mukund (2018)
Geopolymer is a novel material that has wide-ranging applications. While geopolymer could serve as structural material for fire resistance applications, the existing knowledge about influence of mix design factors and tailoring on its high temperature performance needs exploration. This thesis brings to light that by proper tailoring of geopolymer mix design, promising thermal performance could be realized. It enhances the understanding of high temperature response of geopolymers by establishing the relationship between mix design factors and thermal stability of the material at macro-, meso- and micro-scales. The influence of mix design factors on strength endurance, volume stability and chemical stability subject to high temperature exposure for metakaolin-based geopolymer and fly ash-based geopolymer is investigated in depth. Suitable selection of mix design factors and alkali-cation type led to development of fly ash-based geopolymers with promising thermal stability. Moreover, it was found that even using sodium as an alkali cation, not only stable but even enhanced thermal performance could be attained. Significance of this research also lies in discovering the underlying mechanisms governing the thermal performance of geopolymers through application of various experimental techniques such as observation of cracking damage using photography, microstructure using scanning electron microscopy and mercury intrusion porosimetry, deformation using dilatometry and chemical structure using Fourier transform infrared spectroscopy and x-ray diffractometry. Through the understanding gained in this research, it is possible to design geopolymers with good thermal resistance. This systematic study brings us a step forward towards application of geopolymers as a fire- resistant construction material for structural applications.